Determination of Pesticides in Water Sample of Sagar District MP: Assessment of Pesticide Residues in Water Samples from Sagar District, MP (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Pesticides have been utilized broadly by the farmers in India amid the last few decades. As Organochlorine (OCPs) and organophosphorus (OPPs) pesticides have been utilized ordinarily in the horticulture field, a direct and effective strategy for extraction for pesticides utilizing strong stage extraction (SPE) have been developed for detection of OCPs and OPPs in water. Seventeen chose mixes of OCPs and OPPs were removed from water utilizing RP-C18 cartridge and the states of extraction were upgraded. Every one of the pesticides were dissected utilizing gas chromatography-electron caught identifier (GC-ECD). Pesticide deposits identified in ordinary field change from 0.081 to 0.695ggL which is marginally higher than those recognized in natural fields from (0.058 to 0.662) ggL. This is expected for the most part from the truly utilized of pesticides in the plot no pesticide were utilized in the natural plot since the most recent three years. This plainly demonstrates the pesticide deposits in the dirt from recorded utilized can even now taint the natural field ecological.